Electromagnetic Beam Causing Instability - Dr. Amrita (International Journal of Engineering and Management Research, 2021)
In laser, a perturbation in the laser intensity has a tendency to grow. The regions where of intensity is higher, hence the electron density falls and gives rise to a higher refractive index. This region attracts power from neighborhood causing growth of intensity perturbation. Hence we get filaments.